The comparison of reproductive hormone receptor expressions of the sheep ovary and hormone concentrations in two Chinese breeds. Issue 6 (10th May 2019) - Li, Liangyuan; Lu, Shouliang; Ma, Qiman; Wan, Pengcheng; Liu, Changbin; Yang, Hanyulu; Yang, Hua; Yang, Yonglin; Dai, Rong; Shi, Guoqing
Abstract: The aim of this research was to investigate the changes in reproductive hormone receptor expressions of the ovary and hormone concentrations between oestrous cycle pattern of two different sheep breeds in China. Ovarian tissues were collected from Chinese Merino (Junken type) and Hu sheep with different reproductive states in spring and autumn. Serum samples were assayed for oestrogen (E2), progesterone (P), luteinizing hormone (LH) and follicle‐stimulating hormone (FSH) concentrations by radioimmunoassay during spring. The ovarian expression of hormone receptors (ERα, ERβ, PR, LHR and FSHR) was analysed using real‐time reverse transcription polymerase chain reaction (RT‐PCR). In Chinese Merino, there was no corpora lutea and ovulation point on the surfaces of ovaries in spring and low basal levels of both LH and P in serum. ERα, ERβ and FSHR were expressed significantly higher in Merino ovaries during anoestrus compared with oestrous or luteal phases of Hu sheep ( p  < 0.05 or p  < 0.01). However, both varieties of sheep exhibited a similar tendency to secrete E2 and FSH. Compared with Hu sheep, FSH levels were slightly higher in Merino serum. In Hu sheep, ERα, ERβ, FSHR, LHR and PR expressed in luteal phase ovaries during spring were significantly lower ( p  < 0.05, p  < 0.01 or p  < 0.001) than autumn. Interestingly, LHR and PR expressed in anoestrous ovaries were similar to that in oestrous phase of both sheep breeds. The above results suggest that seasonal reproductive sheep increased the expression of E2 and FSH receptors in ovary during spring may enhance the effects of E2 and FSH on follicular development. It is likely that this enhancement prevents the ovary from progressing to the luteal phase.